Multifunctional Titanium Surfaces for Orthopedic Implants: Antimicrobial Activity and Enhanced Osseointegration - Ghilini, Fiorela (2021)
The use of implants in orthopedics and dental practice is a widespread surgical procedure to treat diverse diseases. However, peri-implantitis due to infections and/or poor osseointegration can lead to metallic implant failure. The aim of this study was to develop a multifunctional coating on titanium (Ti) surfaces, to simultaneously deal with both issues, by combining antibacterial silver nanoparticles (AgNPs) and regenerative properties of lactoferrin (Lf). A simple and cost-effective methodology that allows the direct multifunctionalization of Ti surfaces was developed. The modified surfaces were characterized by atomic force microscopy (AFM), X-ray photoelectron spectroscopy, and contact angle measurements. Additionally, in vitro preosteoblast cell adhesion, cell viability, and differentiation were evaluated. The antibacterial capability of the surfaces was tested against Staphylococcus aureus as a prosthesis infection model strain. Our results showed that Lf adsorbed on both Ti surfaces and Ti surfaces with adsorbed AgNPs. Simultaneously, the presence of Lf and AgNPs notably improved preosteoblast adhesion, proliferation, and differentiation, whereas it reduced the bacterial colonization by 97.7%. Our findings indicate that this simple method may have potential applications in medical devices to both improve osseointegration and reduce bacterial infection risk, enhancing successful implantation and patients' quality of life.